2006
DOI: 10.1097/01.brs.0000219867.07683.7a
|View full text |Cite
|
Sign up to set email alerts
|

Coccygectomy For Coccydynia: Case Series and Review of Literature

Abstract: It is possible that degenerate changes in sacrococcygeal discs and/or intercoccygeal discs are associated with pain. Surgical results are better in those with a severe degree of degenerative change. Coccygectomy remains a successful treatment for a majority of severely disabled patients with coccydynia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 17 publications
(19 reference statements)
2
66
0
6
Order By: Relevance
“…According to Bayne et al, 16 15% of their patients presented with preexisting back pain, and Perkins, Schofferman and Reynolds 20 reported that 77% of patients had co-existing lumbar spine disorders. Balain et al 8 reported a 71% incidence of concomitant lumbar spine disorders.…”
Section: Aetiology Of Coccydyniamentioning
confidence: 99%
See 3 more Smart Citations
“…According to Bayne et al, 16 15% of their patients presented with preexisting back pain, and Perkins, Schofferman and Reynolds 20 reported that 77% of patients had co-existing lumbar spine disorders. Balain et al 8 reported a 71% incidence of concomitant lumbar spine disorders.…”
Section: Aetiology Of Coccydyniamentioning
confidence: 99%
“…Balain et al 8 reported that coccydynia had been under-represented, especially as the motivation of some patients was suspect. Bremer 22 was the first to describe the association of neurosis with coccydynia.…”
Section: Aetiology Of Coccydyniamentioning
confidence: 99%
See 2 more Smart Citations
“…Konservatif tedaviye cevap alınamıyorsa cerrahi bir seçenek olabilir. Cerrahi girişim olarak koksektomi (kuyruk sokumu kemiğinin mobil kısmının eksizyonu) uygulanır (6,20,31,40,41). Koksiks eksizyonu Key'in tanımladığı tekniğe göre yapılır.…”
Section: Cerrahi Ve Ameliyat Sonrası Tedaviunclassified